Investigating the inter-rater reliability and usability of telehealth for home hazard falls-risk assessment after stroke - Ainuddin, Husna Ahmad; Romli, Muhammad Hibatullah; Hamid, Tengku Aizan; Salim, Mazatulfazura S. F.; Mackenzie, Lynette (Tehran University of Medical Sciences, 2024)
Introduction: Stroke survivors are more likely to fall at home. A home hazard assessment may be beneficial to reduce the risk of falling; however, it is resourceful and time-intensive. This study examines the inter-rater reliability and usability of telehealth for a hazard assessment to address the risk of falls. Materials and Methods: Two occupational therapists accessed the telehealth platform from different locations and simultaneously rated participants’ home environment using the home falls and accident screening Tool. Stroke survivors and their caregivers answered the telehealth usability questionnaire. Results: A total of 36 stroke survivors and 31 caregivers participated in the study. Gwet’s AC1 was used for agreement analysis. The overall AC1 value for the inter-rater reliability was 0.93 (95% confidence interval [CI], 0.66%, 1.00%). There was a moderate correlation between the raters (r=0.57, P=0.000). Bland and Altman graph plot showed a mean difference of -0.61 and 97.2% of the difference score fell within the limits of agreement (95% CI, -5.67%, 4.39%). The overall mean score of the telehealth usability questionnaire was 5.62 out of 7. Conclusion: Telehealth technology is a potential medium that provides an opportunity for synchronous practitioner-client interaction in evaluating home hazards. Some challenges were noted during the telehealth sessions, thus requiring a brief protocol to navigate the system.